Evaluation of long-term effects of nitrogen fertilizer and rice residue management on soil surface nitrogen budget in a lowland paddy rice - Ku, Hyun-Hwoi; Lee, Sang-Eun; An, Jae-Ho; Kim, Tae-Wan (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2019)
Soil surface nitrogen (N) budget is a useful tool for assessing soil fertility, crop productivity, and environmental quality but it is mainly dependent on farming management practices in agroecosystem. Hence, we evaluated long-term effects of N fertilizer and rice residue management on soil surface N budget in rice cropping system over 28-year using the constructed long-term data set of inputs, outputs, and change in total soil N. To evaluate rice N uptake (RN), loss N (LN), change in total soil N, and the N budget, five rates of N fertilizer (N 0, 100, 150, 200, 250 kg N ha-1 yr-1) under non-rice residue (control) and rice straw (RS) and rice straw compost (RSC) incorporated plots were continuously applied. Results showed that long-term incorporation of RS and RSC contributed to higher RN compared to that under control regardless the given N rates. Although a relatively superior total soil N in RS and RSC other than control was accumulated, LN was increased and varied according to increasing N rates. Meanwhile, less LN from RSC was significant due to comparable accumulation of total soil N content. In determination of the N budget on 28-year average, continuous incorporation of RS and RSC obtained near zero  (− 0.5 kg N ha-1 yr-1 and 0.7 ± 6.0 kg N ha-1 yr-1), while control showed negative by − 54.0 ± 5.6 kg N ha-1 yr-1 due to greater difference in change in total soil N. In conclusion, both of RS and RSC could enhance and maintain total soil N reserve, rice production, and thus N balance, but the adverse impact of N fertilization on the risk of environmental pollutions required for minimizing N loss.